Do Physics Textbooks Present the Ideas of Thought Experiments?: A Case in Indonesia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study sought to check and evaluate whether or not thought experiments presented in the Indonesian physics textbooks can be used as tools to transfer scientific knowledge. This was a descriptive study using Indonesian physics textbooks as the primary sources of data. In this study, we analyzed thirty (30) physics textbooks from Grades 10 to 12 which are widely used both by teachers and students. The results showed that majority of physics textbooks did not mention about thought experiments. Only 6 physics textbooks presented thought experiments at a satisfactory level. The number of physics textbooks that described thought experiments in fair and poor levels are 9 and 5 respectively. The study concludes that Indonesian physics textbooks published from 2009 to 2017 generally lack thought experiments. Many authors of these Indonesian physics textbooks ignored or inadequately present thought experiments. Moreover, 70% of thought experiments mentioned in the physics textbooks were in the fair and poor levels. So, in general, thought experiments presented in the Indonesian physics textbooks cannot be used as an introduction in transferring scientific knowledge to science students.